Respuesta :

Answer:

B, C, and [assumption] E.

Step-by-step explanation:

We are looking for an expression that is equal to -4(6). -4 * 6 = -24.

A. -4(-6)

-4 * -6 = 4 * 6 = 24

So, A does not have the same solution.

B. 4(-6)

4 * (-6) = -24

So, B has the same solution.

C. 6(-4)

6 * (-4) = -24

So, C has the same solution.

D. -8(2)

-8 * 2 = -16

So, C does not have the same solution.

E. 12(-2)

[I am not sure what number it is but I am assuming it is -2]

12 * (-2) = -24

So, assumingly, E has the same solution.

Hope this helps!

Answer: b c e

Step-by-step explanation: